Continuous Vernier filtering of an optical frequency comb for broadband cavity-enhanced molecular spectroscopy. (January 2017) - Rutkowski, Lucile; Morville, Jérôme
Abstract: We have recently introduced the Vernier-based Direct Frequency Comb Cavity-Enhanced Spectroscopy technique which allows us to record broadband spectra at high sensitivity and GHz resolution (Rutkowski and Morville, 2014)[1] . We discuss here the effect of Vernier filtering on the observed lineshapes in the 3 ν + δ band of water vapor and the entire A-band of oxygen around 800 nm in ambient air. We derive expressions for the absorption profiles resulting from the continuous Vernier filtering method, testing them on spectra covering more than 2000 cm −1 around 12, 500 cm −1 . With 31, 300 independent spectral elements acquired at the second time scale, an absorption baseline noise of 2 × 10 − 8 cm − 1 is obtained, providing a figure of merit of 1.1×10 −10 cm −1 / Hz per spectral element with a cavity finesse of 3000 and a cavity round-trip length around 3.3 m. Abstract : Highlights: A recently introduced Cavity-Enhanced Direct-Frequency-Comb Spectroscopy technique is discussed in detail. It relies on the continuous-Vernier-filtering regime, defined in this paper. Spectra with high sensitivity covering 2000 cm − 1 at 2 GHz resolution are obtained. A complete formalism is presented to adjust spectra at atmospheric conditions.